Association of Renal Function (Estimate Glomerular Filtration Rate) with the Number of Febrile Urinary Tract Infections in Children with Neurogenic Bladder - Zhou, Guanglun; Jiang, Man; Zhu, Wenbin; Liu, Xiaodong; Sun, Junjie; Li, Shoulin (European Journal of Pediatric Surgery, 2023)
Introduction Our objective was to evaluate whether renal function, assessed as the estimated glomerular filtration rate (eGFR), is associated with the number of febrile urinary tract infections (FUTIs) in children diagnosed with neurogenic bladder (NB).Materials and Methods Clinical information of patients diagnosed with NB was prospectively collected between January 2013 and January 2022. Episodes of FUTI were recorded during the follow-up period, and the eGFR was calculated based on the serum cystatin C level. Grading (G1–G5) of chronic kidney disease (CKD) was conducted as described by the eGFR.Results In total, 463 children were included in the final analysis (265 males and 198 females; mean age: 23 months). The median follow-up time was 51 months. A total of 302 children had four or more FUTIs and 161 children had none to three FUTIs. The incidence of developing CKD G3 to G5 gradually increased from the first to third (1.3–2.4%) episodes of FUTI and drastically increased after four episodes (≥ 22.5%), with the incidence recorded to be 100% after eight FUTIs. The odds of CKD G3 to G5 in children with four FUTIs were 17.3 and 43.7 times greater after four and six FUTIs, respectively, than in children with one FUTI.Conclusion This study showed that recurrent FUTIs are common in children with NB and that the risk of rapid progression to CKD G3 to G5 increases substantially after four or more FUTIs episodes.
Keywords: renal function; glomerular filtration rate; urinary tract infection; neurogenic bladder